Natural resistance of the rabbit organism under the influence of Eimeria spp. pathogens - M. P. Prus; Y. V. Duda (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Immunity in parasitic diseases has several specific features determined by the interactions within the parasite-host system. The host's immune response can be characterized primarily by changes in the cellular composition of the blood, the overall level of immunoglobulins, and alterations in their qualitative composition. This study aimed to investigate rabbits' cellular and humoral immunity factors under the influence of Eimeria spp. pathogens. The study was conducted on male rabbits aged 3-5 months with varying levels of infestation by Eimeria spp.: Eimeria magna, E. media, E. perforans, and E. stiedae (low level – II = 1838.89 ± 1114.68 oocysts per 1 g of feces, medium level – II = 39787.50 ± 13422.34 oocysts per 1 g of feces, and high level – II = 88578.57 ± 17776.32 oocysts per 1 g of feces). It was established that the parasitism of Eimeria spp. in the organism of rabbits, compared to healthy animals, led to changes in the leukogram of rabbit blood, manifested as leukocytosis (by 1.21 times, 1.26 times, 1.28 times, P < 0.001), absolute lymphocytosis (by 1.22 times, 1.28 times, 1.28 times, P < 0.001), eosinophilia (by 1.67 times, 1.85 times, and 2.04 times, P < 0.001), and basophilia (by 1.83 times, 2.33 times, 2.83 times, P < 0.01–0.001), which, in our opinion, indicates an inflammatory process in the animal's body. A significant (P < 0.01–0.001) increase in the levels of B-lymphocytes (by 1.57 times, 1.71 times, 1.96 times) and T-lymphocytes (by 1.24 times, 1.29 times, 1.26 times), due to T-helpers and T-active cells, against the background of a decrease in the number of T-suppressors and phagocytic activity of neutrophils (by 3.82 %, 5.91 %, 6.92 %, P < 0.05–0.001), may indicate stimulation of the immune system by antigens and the chronic phase of the disease. In the blood of rabbits infected with Eimeria spp. pathogens, there was a significantly higher content of IgA (1.78 times, 1.85 times, 1.97 times, P < 0.001), IgG (1.42 times, 1.65 times, and 1.70 times, P < 0.001), and circulating immune complexes (CIC) levels, against the background of lower levels of BASC, LASC (by 1.26 times, 1.36 times, and 1.49 times, P < 0.001), and KASC. These changes in humoral defense factors suggest the progression of an inflammatory process caused by Eimeria parasitism, the severity of which correlated with the intensity of the invasion.